Experimental investigation of wave-induced motions of an obliquely moving ship - Adnan, Faizul Amri; Hironori, Yasukawa (2008)
The lateral drift appears due to the effects of wind forces and/or wave drifting forces for a ship sailing in actual sea. The effects of wind forces and / or wave drifting forces in views of lateral drift for ship moving with certain forward speed have not been studied previously. Therefore, it is important to investigate experimentally the influence of the lateral drift to ship seakeeping performance. In this paper experimental results for the ship motions and drift forces on a container ship SR108 obliquely moving in waves are presented. An outline of the model test are also presented in this paper. It is shown that sway, yaw and roll motions are significantly occured even in head waves. In general it is also found that the ship motions and drift forces are influenced mostly by hull drift motion.